2021
DOI: 10.3991/ijet.v16i16.23371
|View full text |Cite
|
Sign up to set email alerts
|

Adopting A New Hybrid Force Model: A Survey During Covid-19 In Indian Higher Education

Abstract: This quantitative study proposes and validates the Hybrid force model by analysing the challenges and opportunities in online education during COVID-19 through an online survey from students and teachers of Indian higher education institutions. The proposed model considers the learner as a system of study and talks about the amalgamation of knowledge, human force (teacher), and techno-logical force for better online learning opportunities and experience. The results show Google Meet, Zoom, and Microsoft Team a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…Therefore, learners can engage in online learning without changing their habits, investing additional effort (EE), or incurring high costs (PV); this is vital because lower barriers would increase learners’ BI to continue online learning. Before the pandemic, massive open online courses (MOOCs) were already changing people’s traditional view of online teaching (SI), for online learning becoming students’ preference that made the amalgamation of knowledge, human force (teacher) and technological force ( Ranjan et al, 2021 ). Online learning is no longer the traditional form of non-formal education but a teaching form in which high-quality teaching resources are shared.…”
Section: Discussion and Suggestionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, learners can engage in online learning without changing their habits, investing additional effort (EE), or incurring high costs (PV); this is vital because lower barriers would increase learners’ BI to continue online learning. Before the pandemic, massive open online courses (MOOCs) were already changing people’s traditional view of online teaching (SI), for online learning becoming students’ preference that made the amalgamation of knowledge, human force (teacher) and technological force ( Ranjan et al, 2021 ). Online learning is no longer the traditional form of non-formal education but a teaching form in which high-quality teaching resources are shared.…”
Section: Discussion and Suggestionsmentioning
confidence: 99%
“… Tandon et al (2021) identified the facilitators and inhibitors for the adoption of e-learning for the undergraduate students by structural equation modeling (SEM), found that all the identified facilitators emerged significant except social influence (SI) and price value (PV), and technology risk emerged insignificant while all other inhibitors had significant impact on BI to adopt e-learning. Several researchers from different countries have explore the effectiveness and learners’ perceptions of online learning in higher education during COVID-19 ( Al-Karaki et al, 2021 ; Packmohr and Brink, 2021 ; Peimani and Kamalipour, 2021 ; Ranjan et al, 2021 ). The purpose of this study is to validate the UTAUT2-based e-learning model to comprehensively explore learners’ intention to continue online learning during COVID-19 in China, which is different from the previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…Many platforms are commonly used around the world for online learning. Google meet, Zoom and Microsoft Teams are often used as the main platforms for non-traditional learning [22]. Based on these problems, we tried a new method, namely by designing a mini studio that will be used in the learning process during this pandemic.…”
Section: Intoductionmentioning
confidence: 99%
“…Various methods were also adopted by state university to maintain service quality, including online or virtual learning, student admissions, graduation ceremonies, replacement of the Real Work Lecture projects in the regions with PKL Projects, and quota subsidies for student (Arfiyansyah, 2021). The transition to virtual learning was a significant transformation in the educational process (Chamorro-Atalaya et al, 2022;Ranjan et al, 2021). Moreover, the volatile economic conditions necessitated financial relief for student affected by the pandemic and the reallocation of study funds toward health and economic recovery (Arfiyansyah, 2021).…”
Section: Introductionmentioning
confidence: 99%